2006
DOI: 10.4049/jimmunol.176.3.1962
|View full text |Cite
|
Sign up to set email alerts
|

Effacing of the T Cell Compartment by Cardiac Transplantation in Infancy

Abstract: For cardiac transplantation in infants, T cells are depleted and the thymus is removed. These manipulations should cause profound defects in the T cell compartment. To test this concept, 20 subjects who underwent cardiac transplantation in infancy and healthy age-matched subjects were studied. The number of T cells in the blood was nearly normal in all subjects 1–10 years after surgery. However, newly generated T cells were undetectable in 10 recipients and 10-fold less than controls in 10, suggesting absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 41 publications
6
51
0
Order By: Relevance
“…We (15) have found that human subjects who undergo cardiac transplantation in infancy have profound contraction of the TCR repertoire, with diversity of V␤ being as low as 10 4 (compared with 10 6 in age matched controls), but do not suffer a heightened risk of disseminated viral infections or of infections with opportunistic organisms or tumors compared with other transplant recipients. In the course of cardiac transplantation (or nontransplant cardiac surgery) early in life, the thymus is removed and the recipient is treated with Thymoglobulin or anti-CD3 to deplete mature T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We (15) have found that human subjects who undergo cardiac transplantation in infancy have profound contraction of the TCR repertoire, with diversity of V␤ being as low as 10 4 (compared with 10 6 in age matched controls), but do not suffer a heightened risk of disseminated viral infections or of infections with opportunistic organisms or tumors compared with other transplant recipients. In the course of cardiac transplantation (or nontransplant cardiac surgery) early in life, the thymus is removed and the recipient is treated with Thymoglobulin or anti-CD3 to deplete mature T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TCR repertoire contracts profoundly with age (14) and elderly individuals can suffer disseminated viral infections and heightened susceptibility to tumors, most elderly individuals experience neither of these ailments (compared with those who have AIDS). Still more dramatic is the observation that those who undergo cardiac transplantation in infancy and have a profound contraction of the TCR repertoire owing to "total" thymectomy and mature T cell depletion suffer no excess of opportunistic infections or tumors (15).…”
mentioning
confidence: 99%
“…Previous short-term surveys showed that thymectomized children have reduced CD4 + T cell and TCR excision circle numbers compared with age-matched controls (6)(7)(8)(9)(10). More recently, reduction of naive CD4 + T cell numbers and production in thymectomized patients was shown to correlate with chronological age and time since thymectomy (11).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of PBMC samples from YATECs, taken an average of 2 decades after thymectomy, revealed clear alterations in the CD4 + T cell compartment (as expected from previous studies on CHD patients; ref. [6][7][8][9][10][11] as well as in the CD8 + T cell compartment. We found decreased CD4 + and CD8 + T cell counts in YATECs compared with age-matched controls, and even compared with middle-aged adult controls (Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
“…32 We also showed that under physiological conditions, diversity of T cells in humans correlates directly with the level of thymic function and correlates with the level of TREC in blood. 33,34 We focused our analyses on the human a chain of the TCR because porcine b chain of the TCR is quite homologous with human. A primer specific for the human a chain was used to extract TCRVa-specific RNA from PBMC, which was biotinylated and applied to a gene chip.…”
Section: Diversity Of Human T Cells In Chimeric Swinementioning
confidence: 99%